Synthesis, Characterization and Thermal Decomposition Studies of Cr(III), Mn(II) and Fe(III) Complexes of N, N '-Bis[1,3-benzodioxol-5-ylmethylene]butane-1,4-diamine - Prasad M. Alex; K. K. Aravindakshan (E-Journal of Chemistry)
A bidentate Schiff base ligand namely, N,N'-bis-1,3-benzodioxol-5-ylmethylene]butane-1,4-diamine was synthesised by condensing piperonal (3,4-dioxymethylenebenzaldehyde) with butane-1,4-diamine. Cr(III), Mn(II), Fe(III) complexes of this chelating ligand were synthesised using acetates, chlorides, bromides, nitrates and perchlorates of these metals. The ligand and the complexes were characterised by elemental analysis, 1H NMR, UV-Vis and IR spectra, conductance and magnetic susceptibility measurements and thermogravimetric analysis. The thermograms of three complexes were analysed and the kinetic parameters for the different stages of decompositions were determined.